PENGARUH METODE INQUIRY-BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA SEKOLAH DASAR - Farikhah Salsa Billah; Rachmatullah, Reza (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the inquiry-based learning method on elementary school students' critical thinking skills. The background of this study is the low critical thinking skills of elementary school students, with approximately 70% of elementary school students still in the low to very low category due to the dominance of conventional, teacher-centered learning methods. The study used a quantitative approach with a quasi-experimental Nonequivalent Control Group Design. The study population was 50 fifth-grade students at SDN Tenggilis Mejoyo 1 Surabaya, divided into two classes: class VA as the control class (conventional learning) and class VB as the experimental class (inquiry-based learning method). Data were collected through pretest and posttest descriptive tests, then analyzed using normality tests, homogeneity tests, and Independent Sample T-Tests with SPSS. The results of the study showed that the experimental class experienced a much more significant increase in average scores compared to the control class, which only experienced a very small increase. The results of the Independent Sample T-Test showed a significance value below the specified error level, so H₀ was rejected and H₁ was accepted. It can be concluded that the inquiry-based learning method has a positive and significant effect on the critical thinking skills of elementary school students, so it is recommended as an alternative innovative learning method in elementary schools. Hasil penelitian menunjukkan kelas eksperimen mengalami peningkatan rata-rata nilai yang jauh lebih signifikan dibandingkan kelas kontrol yang hanya mengalami peningkatan sangat kecil. Hasil uji Independent Sample T-Test menunjukkan nilai signifikansi di bawah taraf kesalahan yang ditetapkan, sehingga H₀ ditolak dan H₁ diterima. Dapat disimpulkan bahwa metode inquiry-based learning berpengaruh positif dan signifikan terhadap kemampuan berpikir kritis siswa sekolah dasar, sehingga direkomendasikan sebagai alternatif metode pembelajaran inovatif di sekolah dasar.